Relationship between lipid profile parameters, coagulation system and inflammation markers in patients with hypertension and multifocal atherosclerosis - S. S. Vedenskaya; E. M. Vishneva; A. A. Kuryndina; N. V. Tagiltseva; D. A. Isakova; O. M. Polyakova; O. G. Smolenskaya (Российский кардиологический журнал)
Aim. To establish the relationship between lipid profile parameters, coagulation system and inflammation markers in patients with hypertension (HTN) and multifocal atherosclerosis (MFA).Material and methods. The study included 110 patients with HTN and MFA with a median age of 59 (51,0;64,3) years. Of these, 15 patients achieved target lowdensity lipoprotein cholesterol (LDL-C) <1,8 mmol/l (group 1), and 95 patients had LDL-C >1,8 mmol/l (group 2). Patients in both groups received lipid-l owering and comparable antihypertensive, antiplatelet therapy. To identify coagulation disorders, a test was performed on the T-2 Thrombodynamics Analyser System (OOO GemaCor, Moscow, Russia). All study participants were assessed for levels of high-sensitivity C-reactive protein and interleukin-6.Results. Despite the lipid-l owering therapy, most patients with HTN and MFA (86,4%) did not achieve target LDL-C <1,8 mmol/l. In patients of group 2, compared to group 1, more pronounced procoagulant shifts were noted. The clot growth rate and the permanent clot growth rate were shifted to the hypercoagulation (28,6 μm/min vs 27 μm/min). Correlations between the studied parameters were also revealed. In group 1, the LDL-C level had a moderate direct correlation with the initial clot growth rate (r1=0,54, p1=0,04) and clot density (r1=0,55, p1=0,03), while in group 2, the concentrations of total cholesterol and LDL-C correlated with clot growth delay (r2=-0,22, p2=0,03 and r2=-0,21, p2=0,04, respectively).Conclusion. In patients with HTN and MFA, complex relationships between lipid parameters, coagulation parameters, and inflammatory markers are observed, especially in the group with unachieved lipid target levels. Extra efforts are needed to identify patients with HTN and MFA in clinical practice and to prescribe optimal lipid-lowering therapy. In addition to lipid parameters, correction of other disorders (hemostasis, inflammation) that may affect the prognosis is necessary.